Bioinformatics-Based Discovery of CKLF-Like MARVEL Transmembrane Member 5 as a Novel Biomarker for Breast Cancer - Zhou, Juan; Lei, Jian; Wang, Jun; Lian, Chen-Lu; Hua, Li; He, Zhen-Yu; Wu, San-Gang (Frontiers in Cell and Developmental Biology, 2020)
Chemokine-like factor-like MARVEL transmembrane members (CMTMs) represent a novel protein family linking the chemokine and transmembrane-4 superfamily families, which potentially play several roles in diverse physiological and pathological processes. The detailed functions and underlying molecular mechanisms of CKLF-like MARVEL transmembrane members (CMTMs) remain elusive in breast cancer. Herein we performed a comprehensive bioinformatic analysis to investigate the prognostic effect, potential functions, and biomolecular regulatory network of CMTMs in breast cancer. The mRNA expression level of CMTM5, in particular, was significantly downregulated in breast cancer; moreover, high mRNA expression level of CMTM5 was significantly associated with better relapse-free survival. DNA promoter hypermethylation of CMTM5 was negatively correlated with its mRNA expression levels. Furthermore, CMTM5 strongly associated with pathway in MARVEL domains, chemotaxis, cytokines, transmembrane structures, and integral component of membrane. For example, genes related to MARVEL domains, transmembrane structures, and chemokines were significantly enriched. Our findings indicate that CMTM5 can be used as a prognostic biomarker and potential therapeutic target for breast cancer.